ISOLASI DAN IDENTIFIKASI BAKTERI LIMBAH MINYAK BUMI DARI PERAIRAN PELABUHAN SUNGAI DUKU KOTA PEKANBARU SEBAGAI RANCANGAN MODUL PEMBELAJARAN BIOLOGI SMA - Butar-Butar, Istami Hiqma; Sayuti, Irda; ', Nusrsal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The study was conducted to determine the isolation and identification of bacteria petroleum waste Sungai Duku port city of Pekanbaru and its potential as a learning module design in senior high school biology in Juny to September 2016. This researchy was conducted two phases: the field research and planning stages of learning modules. This research is descriptive and conducted by examination in the laboratory. The sampling technique in this study, done by using purposive sampling method. The results showed that the isolated bacteria were found in the waters of the Sungai Duku port city of Pekanbaru consists of five genera namely Enterobacter, Acinetobacter, Citrobacter, Klebsiella, and Bacillus. Based on the analysis of the potential of the research results can be used as a module designed on eubacteria concept for senior high school students.